Antimicrobial effect against Aggregatibacter actinomycetemcomitans of advanced and injectable platelet-rich fibrin from patients with periodontal diseases versus periodontally healthy subjects - Thuy Anh Vu Pham; Thao Thi Phuong Tran (Elsevier, 2023)
Objectives: Advanced platelet-rich fibrin (A-PRF+) and injectable platelet-rich fibrin (i-PRF) have recently been developed and used in periodontal therapy. Few studies have contrasted the antibacterial effectiveness of these autologous materials derived from individuals with healthy gums, gingivitis, and periodontitis. This study aimed to compare the antimicrobial effects of these PRF materials against the periodontal pathogenic bacterium Aggregatibacter actinomycetemcomitans (Aa) in patients with different periodontal conditions. Methods: Blood samples were collected from periodontally healthy individuals, patients with gingivitis, or patients with periodontitis to prepare A-PRF+ and i-PRF. The antibacterial capacity of these materials was evaluated through antibiofilm formation, biofilm susceptibility, and the time-kill assay over a 48-h period. Results: A-PRF+ and i-PRF from each patient groups interfered with Aa's ability to form biofilm on the test tube surface, and the effect of i-PRF was significantly different among the patient groups. In contrast, these plasma preparation had a weak impact on mature biofilm. For products from the gingivitis and periodontitis groups, these effects were significantly stronger for i-PRF than A-PRF+ (p = 0.012 and p = 0.004, respectively). All plasma preparations inhibited Aa growth in the first 12 h after application, and i-PRF exhibited a significantly greater antimicrobial effect than A-PRF + at each time point. Conclusion: A-PRF+ and i-PRF in all three patient groups could inhibit the growth of Aa in vitro, and i-PRF from patients with periodontitis exhibited a more significant effect than PRF from the other groups.